2005
DOI: 10.1016/j.febslet.2005.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of GCMa and syncytin via cAMP mediated PKA signaling in human trophoblastic cells under normoxic and hypoxic conditions

Abstract: Glial cells missing a (GCMa) belongs to a new transcription factor family. Syncytin was shown to be a target gene of GCMa. Here, we demonstrate that the protein kinase A (PKA) pathway acts upstream of GCMa. After transient transfection of BeWo cells with PKA, GCMa transcriptional activity and both GCMa and syncytin transcripts were upregulated. This increase was accompanied by further cellular differentiation. Using normoxic or hypoxic conditions to mimic pathophysiological settings known to diminish trophobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 40 publications
7
108
1
3
Order By: Relevance
“…At the transcriptional level, GCM1 was shown to be regulated by a functional cAMP-responsive element and a histone deacetylase 3-binding motif in the promoter region upstream of the start codon. 21,23,24 GCM1 was shown to regulate the expression of different proteins, such as the placental growth factor, 25 a human aromatase, 26 and the fusion protein, Syncytin1. 13 A GCM1-binding motif was also found in the promotor of the human chorionic gonadotropin a-subunit.…”
Section: Discussionmentioning
confidence: 99%
“…At the transcriptional level, GCM1 was shown to be regulated by a functional cAMP-responsive element and a histone deacetylase 3-binding motif in the promoter region upstream of the start codon. 21,23,24 GCM1 was shown to regulate the expression of different proteins, such as the placental growth factor, 25 a human aromatase, 26 and the fusion protein, Syncytin1. 13 A GCM1-binding motif was also found in the promotor of the human chorionic gonadotropin a-subunit.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of the placental cAMP/PKA cascade in up-regulated fusogenic gene expression and differentiation-associated hCG production is well established (Keryer et al, 1998;Knerr et al, 2005; A c c e p t e d M a n u s c r i p t 11 also evaluated. Results showed that incubation of BeWo cells with forskolin for 24h in the presence of SB202190 or U0126 significantly attenuated hCG secretion by 40-55% (Fig.6a).…”
Section: Contribution Of Mapk Cascades In Bewo Hormonogenesismentioning
confidence: 99%
“…Indeed, in placental trophoblasts, PKA has been shown to be an important mediator of fusogenic gene expression as well as hCG induction (Keryer et al, 1998;Knerr et al, 2005;Knöfler et al, 1999). In BeWo trophoblasts, the signalling molecules activated in response to adenylyl cyclase activation were investigated.…”
Section: Signalling Pathways Activated By Forskolinmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that in JEG-3 cells the PMA-induced PKC-and MEK/ ERK-dependent pathway stimulates hCG production but much less so than the FSK-induced cAMPdependent pathway. The cAMP-dependent pathway has been shown to increase the expression level and transcriptional activity of GCMa in trophoblast cells (6,7,27), leading to trophoblast differentiation. In contrast, the PKC-and MEK/ERK-dependent pathway enhances GCMa degradation as well as transcriptional activity.…”
Section: The Pma-induced Pkc-and Mek/erk-dependent Pathway May Enhancmentioning
confidence: 99%